Enacting affirmative critique: exploring the conjunctions and overlaps among Actor-network theory and Feminist New Materialist methodologies - Moberg, Emilie (Reconceptualizing Educational Research Methodology, 2018)
This paper elaborates on alternative versions of critique as produced in an ethnographic field work on the everyday life of a curriculum text in a Stockholm preschool. Assisted by Actor-network theory and Feminist New Materialist methodologies, the paper evolves around three empirical moments where the researcher is depicted as needing to rely on the relational efforts of children, Minecraft figures, concepts, teachers and conversations over coffee. In the paper, Actor network theory and Feminist New Materialist methodologies help to enact alternative versions of critique where dependency and vulnerability is taken as resource. Moreover, a focus on relations and overlaps among entities creates knowledge where for example children and texts are allowed to be strong and vulnerable at the same time.